(untitled) (Praxis Educativa, 2025)
The article presents an innovative approach in relation to the use of artificial intelligence (AI) in higher education, focusing on its role as a teammate in group tasks. Although AI is widely used to personalize learning and automate processes, few studies report its performance as an active collaborator in academic activities. An academic task is described in which an AI-based virtual assistant collaborates with students in group organization, recognition of strengths, distribution of roles, time planning, and review of the final product. The potential of the task is highlighted to promote transversal skills such as teamwork, time management and the use of digital tools. Examples of interactions between students and AI are included, highlighting the potential of the model to enrich learning and the development of transversal competencies. Future research is suggested to evaluate its effectiveness.